Case Report: A 62-Year-Old Woman With Contrast-Induced Encephalopathy Caused by Embolization of Intracranial Aneurysm - Zhang, Ying; Zhou, Ming; Wang, Dong; Liu, Tao; Chang, Pengfei; Zhang, Jie; Zhang, Rui; Luo, Yumin; Liu, Ping (Frontiers in Surgery, 2021)
Contrast-induced encephalopathy (CIE) is a rare complication of endovascular treatment, and is extensively reported as a transient and reversible phenomenon. This report describes a 62-year-old female for an internal carotid artery (ICA) aneurysm embolization. The operation was successful, but postoperation the patient suffered consciousness, blindness, hemiplegia, ophthalmoplegia, fever and seizures. Computer tomography (CT) of the brain without the contrast showed oedema widespread in the right cerebral hemisphere, involved the frontal, parietal, temporal and occipital lobes. She was diagnosed with CIE in time and treated with supportive management as soon as possible, fortunately the patient improved a benign course and was discharged without any neurological deficits. The article emphasizes the prevention of the CIE, as well as the importance of early diagnosis and symptomatic treatment.